An unusual retained object post laser flexible ureteroscopy (retained broken tip of disposable ureteroscope) - Nora, Alsedrani (Urol Case Rep, 2019)
Flexible Ureterorenoscopy (F-URS) has dramatically changed the era of Renal stone management. One of its rare complications is retained objects. Some reports, described accidental breakage is reusable ureteroscope. Here we present 36-year-old male patient who underwent to F-URS in another institute March 2018. Four months later presented to our hospital with right flank pain. Renal Us showed mild hydronephrosis associated with 13 mm renal stones. Patient underwent F-URS, when we found the broken tip of disposable ureteroscope retained from the first operation. Urologist should always pay careful attention to the flexible ureteroscpe to check for any sign of breakage before and after the procedure.